Using web questionnaire for web-based course evaluation: advantages and disadvantages - Fariborzi, Elham; Abu Bakar, Kamariah; Kasa, Zakaria; Abu Samah, Bahaman; Abdullah, Muhammad Taufik (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
The technology for Web questionnaire which have been used for survey research is still young and difficult. Creating and conducting a Web survey is a task requiring familiarity with Web programmes and database. This article examines some advantages and disadvantages of conducting Web survey research especially for Web-based course evaluation at Iranian university E-learning centers. It explores current features and issues associated with Web questionnaire through the implementation of a Web questionnaire for evaluating the effectiveness of computer courses at Iranian university E-learning centers. The findings show that this method had more response rate compared to other methods. It also shows advantages & disadvantages of Web surveys. It can be concluded that Web survey researchers should conduct a careful assessment of their research goals, consider some algorithms and tricks to increase the credibility and response rate through Web questionnaire. In addition, before choosing a specific Web questionnaire or developing one, the timeline for data collection through Web survey, and the financial situation should be considered.